Determining Whether Tai Chi Chuan Is Related to the Updating Function in Older Adults: Differences Between Practitioners and Controls - Yang, Yuan; Chen, Tingting; Wang, Chen; Zhang, Ji; Yuan, Xiaoxia; Zhong, Xiaoke; Yan, Shoufu; Jiang, Changhao (Frontiers in Public Health, 2022)
Background Tai Chi Chuan (TCC) is an effective method for delaying cognitive decline in older adults. However, in older adults, the association between long-term TCC practice and working memory updating has not been extensively studied. Objective This cross-sectional study investigated how updating function operationalized via Reaction Times (RTs) and Accuracy Rates (ARs) of N-Back tasks being measured in a laboratory setting is related to long term practice of TCC. Methods Twenty-six healthy elderly people participated in this experiment. According to the duration of time TCC was practiced, 13 subjects in the TCC group had more than 5 years of experience with TCC exercise, and 13 elderly subjects who had not been systematically exposed to mind-body exercise were assigned to the control group. The N-back task was administered to every participant to evaluate the updating function. Results The TCC group had faster RTs than the control group (p < 0.05). For the 1-back task, the TCC group showed faster RTs than the control group; for the 2-back task, the TCC group exhibited faster RTs than the control group. The TCC group had higher ARs than the control group (p < 0.05). For the 1-back task, the TCC group showed higher ARs than the control group; for the 2-back task, the TCC group exhibited higher ARs than the control group. Conclusions Long-term TCC practitioners exhibit a better updating function as compared to controls who did not practice TCC. Thus, our findings suggest that long-term TCC positively influences the updating function of older adults, making it, in turn, an effective mind-body exercise to maintain specific aspects of cognitive functioning.